The stratified evolution of a cool star. Issue 1 (6th February 2013) - Michaud, G.; Richer, J.; Richard, O.
Abstract A low mass star usually experiences stratification and abundance anomalies during its evolution. A 0.95 M⊙ star with a metallicity Z = 0.004 is followed from the main–sequence to the horizontal branch (HB). On the main sequence the larger effects of stratification may come from accretion as was suggested in relation to metallicity and planet formation. As it evolves through the giant branch, stratification appears around the hydrogen burning shell. It may create hydrodynamic instabilities and be related to abundance anomalies on the giant branch. After the helium flash the star evolves to the HB. If it loses enough mass, it ends up a hot HB star (or in the field an sdB star) with effective temperatures larger than 11000 K. All sdB stars are observed to have approximately solar iron abundance whatever their original metallicity, implying overabundances by factors of up to 100. So should the 0.95 solar mass star. How its internal hydrodynamic properties on the main sequence may influence its fate on the HB is currently uncertain. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)